Analiza zmian preferencji konsumentów wobec produktów spożywczych w procesie integracji z Unią Europejską na przykładzie rynku napojów - Lewińska, Anna (Analysis of Customers' Preference Change to Food Products in the European Union Integration Process on the Example of Non-Alcoholic Drinks, 2005)
The European Union integration process influences Polish market of food products. A situation and changes in preference of customers' taste for non-alcoholic drinks market are analysed in this article. The research has been done on inhabitants of West Pomerania who are 20-24 years old. The method of the Analytic Hierarchy Process is used in the calculation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 21-24